INTRODUKSI FORMULA PUPUK HAYATI BERBAHAN AKTIF PSEUDOMONAD FLUORESCENT ISOLAT PF-122 UNTUK MENINGKATKAN PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI DI LAPANG - Wuryandari, Yenny; Wiyatiningsih, Sri; ., Maroeto (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Introduction of biofertilizer containing pseudomonad fluorescent isolate Pf-122 as active ingredient for improving growth and production of chili plant in the field.Some biological control agents required an efficient formulation required to be apply on large scale in the field. The purpose of this research is to review some biofertilizer formulations form of active ingredients pseudomonad fluorescent Pf-122 which can increase growth and production chilli in the field. The research using Randomized Complete Block Design (RCBD) which consists three kinds of formulation. The formulations are powder, granules and pellets. Chilli without formulations as a control. The best results was growth and production of chilli can be showed from plant height, branch number, productive branch number, fruit number, and fruit weight which was given powder formulation. The results of fruit number, the powder formulation which is given can produce double chilli yield than yield from control plant. Moreover, weight fruit from chilli which is given powder formulation can produce fourfold yields. Growth and production chilli which is given others formulations such as granules and pellets were not significantly different results. The overall result of this research, the best formulation to increase growth and production of chilli in the field was formulations contain active biopesticide pseudomonad fluorescent Pf-122 in powder.